2018
DOI: 10.1104/pp.18.00126
|View full text |Cite
|
Sign up to set email alerts
|

Root Gravitropism Is Regulated by a Crosstalk between para-Aminobenzoic Acid, Ethylene, and Auxin

Abstract: Plants respond to gravitational force through directional growth along the gravity vector. Although auxin is the central component of the root graviresponse, it works in concert with other plant hormones. Here, we show that the folate precursor paraaminobenzoic acid (PABA) is a key modulator of the auxin-ethylene interplay during root gravitropism in Arabidopsis (Arabidopsis thaliana). In gravistimulated roots, PABA promotes an asymmetric auxin response, which causes the asymmetric growth responsible for root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 87 publications
1
35
0
Order By: Relevance
“…Interestingly, folate has previously been reported to influence auxin distribution during seedling development, together with sucrose 59 . Furthermore, it was recently shown that root gravitropism is regulated by a crosstalk between PABA (product of the ADCS + ADCL reaction), ethylene and auxin in Arabidopsis 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, folate has previously been reported to influence auxin distribution during seedling development, together with sucrose 59 . Furthermore, it was recently shown that root gravitropism is regulated by a crosstalk between PABA (product of the ADCS + ADCL reaction), ethylene and auxin in Arabidopsis 60 .…”
Section: Discussionmentioning
confidence: 99%
“…It will be of great interest in future studies to investigate New Phytologist the distribution and dynamics of compound uptake, which could potentially be observed by their labelling, fluorescently or otherwise. Interestingly, the amino acid para-aminobenzoic acid, which has a similar structure to AA and is produced from the same precursor, has also recently been shown to play a role in root gravitropism, distinct from its better known role in folate biosynthesis (Nziengui et al, 2018). However, unlike AA, para-aminobenzoic acid promotes gravitropic root growth in WT plants as well as promoting gravistimulated root bending by enhancing the asymmetric auxin response between the two root sides (Nziengui et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the loss of this enzyme would lead to the inability to produce essential folate which would reduce the plant viability dramatically. Interestingly, pABA is also involved in the regulation of root gravitropism (Nziengui et al, 2018). This implies a modulatory role of AtDAT in differential root growth including gravitropism, which can be tested in future by the analysis of our dat1 mutants and accessions without or reduced AtDAT1 activity.…”
Section: Discussionmentioning
confidence: 95%
“…For tobacco leaf infiltration transformed Agrobacterium containing pUB10-GFP::DAT1 was mixed with a strain of transformed Agrobacterium for expression of the mCherry plastid marker (CD3-999 pt-rk; Nelson et al, 2007) and P19 A. tumefaciens cells into infiltration media [10 mM MES-KOH (pH 5.7), 10 mM, MgCl 2, 0.2 mM Acetosyringone]. Using a syringe 1 ml of infiltration media with the mix of the three types of cells was infiltrated in the abaxial side of Nicotiana benthamiana leaves.…”
Section: Arabidopsis Transformation and Tobacco Leaf Infiltrationmentioning
confidence: 99%